2015
DOI: 10.1039/c5lc00609k
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone dongle for simultaneous measurement of hemoglobin concentration and detection of HIV antibodies

Abstract: It is traditionally difficult to incorporate two classes of diagnostic tests into a single platform. In this work, we demonstrate a microfluidic-based smartphone dongle that simultaneously measures concentration of hemoglobin and detects HIV antibodies. Specifically, we demonstrate how a previously published immunoassay device, which measured optical density of silver precipitation on gold colloids, can be expanded to quantitatively measure hemoglobin concentration via a colorimetric assay. By lysing whole blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 15 publications
0
54
0
Order By: Relevance
“…77 In this system, an immunoassay device was expanded to quantitatively detect hemoglobin concentration and HIV antibodies through colorimetric measurement of the optical density of silver precipitation on gold nanoparticles. It has been demonstrated that the HIV immunoassay in the presence of CHAPs detergent could have 95% specificity and 95% sensitivity.…”
Section: Cell Phone-based Dongle Platformmentioning
confidence: 99%
“…77 In this system, an immunoassay device was expanded to quantitatively detect hemoglobin concentration and HIV antibodies through colorimetric measurement of the optical density of silver precipitation on gold nanoparticles. It has been demonstrated that the HIV immunoassay in the presence of CHAPs detergent could have 95% specificity and 95% sensitivity.…”
Section: Cell Phone-based Dongle Platformmentioning
confidence: 99%
“…For reasons including convenience and privacy, reproductive health has already proven to be an important area for decentralizing blood testing. This practical and promising study of Nosrati et al complements other next-generation diagnostic tests for reproductive health that have been tested on clinical samples (4,5,7,8 ), as well as recently approved home tests such as the HIV test (9 ). More broadly, advances such as the test reported by Nosrati et al could dramatically expand the capabilities of consumer health testing devices, which are already prevalent for activity tracking and personalized genomics testing.…”
mentioning
confidence: 91%
“…13 This approach has been replicated in platform based on a smartphone, in which the built-in camera sensor detects light transmission through a cuvette or microfluidic device. 14,15 Alternatively, some methods use paper to absorb treated blood prior to performing a colorimetric analysis. 16,17 In addition, a centrifugal microfluidics platform uses rigorous mixing of whole blood and chemicals prior to optical readouts.…”
Section: Introductionmentioning
confidence: 99%